Canine osteosarcoma cells exhibit resistance to aurora kinase inhibitors. (15th February 2013) - Cannon, C. M.; Pozniak, J.; Scott, M. C.; Ito, D.; Gorden, B. H.; Graef, A. J.; Modiano, J. F.
Abstract We evaluated the effect of Aurora kinase inhibitors AZD1152 and VX680 on canine osteosarcoma cells. Cytotoxicity was seen in all four cell lines; however, half‐maximal inhibitory concentrations were significantly higher than in human leukaemia and canine lymphoma cells. AZD1152 reduced Aurora kinase B phosphorylation, indicating resistance was not because of failure of target recognition. Efflux mediated by ABCB1 and ABCG2 transporters is one known mechanism of resistance against these drugs and verapamil enhanced AZD1152‐induced apoptosis; however, these transporters were only expressed by a small percentage of cells in each line and the effects of verapamil were modest, suggesting other mechanisms contribute to resistance. Our results indicate that canine osteosarcoma cells are resistant to Aurora kinase inhibitors and suggest that these compounds are unlikely to be useful as single agents for this disease. Further investigation of these resistance mechanisms and the potential utility of Aurora kinase inhibitors in multi‐agent protocols is warranted.